T25. THE RELATIONSHIP BETWEEN AGE AT FIRST-EPISODE AND LONGITUDINAL CORTICAL CHANGES IN FIRST-EPISODE PSYCHOSIS: A TWO-YEAR LONGITUDINAL STUDY IN AN ADOLESCENT AND ADULT-ONSET COHORT. (18th May 2020) - Santonja, Javier; Pina-Camacho, Laura; Martínez, Kenia; Díaz-Caneja, Covadonga; Arango, Celso; Bernardo Arroyo, Miguel; Mezquida, Gisela; Janssen, Joost; Parellada, Mara
Abstract: Background: In a unique deeply phenotyped longitudinal dataset consisting of first-episode psychosis (FEP) patients with a wide age at FEP onset (15 to 35 years) and healthy controls, we aimed to determine whether cortical abnormalities are already present at FEP, whether they progress further over the first two years of the illness, and, if so, whether change patterns are associated with age at first episode. Methods: Multicenter (four-site) two-year follow-up case-control brain magnetic resonance imaging study; 74 patients with a FEP of less than 12 months' duration, and 64 healthy controls (matched for age, sex, parental socioeconomic status and handedness) were scanned twice (median time between baseline and follow-up scan 24 months, range [16 – 32]). We computed percentage changes (PC) over follow-up in thickness/area/volume for frontal, temporal, parietal and occipital lobes. We included diagnosis (patient vs. control), age at baseline scan, sex, TBV and site as potential confounders. We conducted post-hoc comparisons for young (≤19y) and adult (>19y) diagnostic pairs (FEP vs healthy controls). Results: A significant age-by-diagnosis interaction was only found for temporal lobe cortical thickness (CT)-PC (d = -.54, p = .002). Within this lobe, the largest effects for the age x diagnosis interaction were found in the middle (d = -.43, p = .01) and inferior (d = - .48, p = .007) temporal gyrus CT-PC. The younger the patient group, the greater temporal thinning relative to their age-matched control group. The most extreme patient vs. control PC difference (i.e. the largest effect size) was found at an age cut-off of 19 years (d=0.9, p= .01). Discussion: In individuals with psychosis, the two-year cortical changes that follow the FEP are dependent of age at first episode, with those with an earlier onset showing more severe cortical thinning in the temporal lobe.